WORKSHOP TENTANG PENYUSUNAN ALAT EVALUASI BELAJARBAHASA JERMAN MELALUI PROGRAM íœBUNGSBLí„TTER PERMAUSKLICK BAGI GURU BAHASA JERMANANGGOTA IGBJI MALANG - S.Pd. M.Hum., M. Kharis, (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2012)
Training in arrangement and development of an evaluation devicethrough íœbungsblätter Per Mausklick is important to do for supporting teachersin the arrangement and development of an evaluation device in teaching theGerman language. The methods used in this activity include training sessions,question-and-answer session, and demonstrations in the form of workshopwhich refers to developed modules. The arrangement of test types and forms istrained and practiced step by step. The types and the form of the test includefilling Präposition, Konjunktion, Personalpronomen, Bestimmte/UnbestimmteArtikel, Possessivartikel, Demonstrativartikel, Modalverben, Negation, andAuxillary.After undergoing this activity, teachers are expected to (1) acquire somenew knowledge and have capability in operating the íœbungsblätter PerMausklick program; (2) gain the knowledge about arranging their evaluationdevice using this program. Indeed, the knowledge is useful for developing aGerman language question bank into various types of evaluation device orvarious types of German language test.